PENGARUH EFIKASI DIRI DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN TAHUN AKADEMIK 2018/2019 UNIVERSITAS FLORES ENDE, NTT: Pengaruh Efikasi Diri dan Pendidikan Kewirausahawan - Ariswan Usman Aje; Lely Suryani; Kristianus Jago Tute (Universitas Putera Batam, 2019)
ABSTRACT The problem in this research is the lack of interest in student entrepreneurship to graduate graduates. This causes many educated unemployed, the thought of students and graduates is that they can work, without thinking about how they create their own jobs. The method in this study is a survey method with a quantitative approach, samples were taken randomly with 84 students using the Slovin formula from a population of 106 students. Data collection techniques in the form of instruments in the form of a Likert scale questionnaire documentation and observation. Analysis techniques in this study are quantitative using descriptive statistics, and subsequently using multiple linear regression, classical assumptions and hypothesis testing. From the results of the analysis table above the effect of Self-Efficacy (X1) on Entrepreneurial Interest (Y) obtained t Count = 0.298 <t table 3.110 with the value of sig. = 0.767, because the significance is greater than 0.05, which is 0.767), namely rejecting H1, the effect of entrepreneurship education on entrepreneurial interest with a value of t Calculate = 7.631> t Table 3.110, because the significance is less than 0.05, 0.000 and accept H1. Simultaneously the F Test Result is 29,137> from 3,110 F Table with a significance level of 0,000 <0.05, it can be concluded rejecting H0. Thus there is an effect between Self-Efficacy and Entrepreneurship Education simultaneously influencing the Interest of Entrepreneurship by 41.8% and receiving H1